2022
DOI: 10.1155/2022/1089722
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evaluation of Nonsynonymous SNPs in Human ADAM33: The Most Common Form of Genetic Association to Asthma Susceptibility

Abstract: ADAM33 is a zinc-dependent metalloprotease of the ADAM family, which plays a vital biological role as an activator of Th2 cytokines and growth factors. Moreover, this protein is crucial for the normal development of the lung in the fetus two months after gestation leading to determining lung functions all over life. In this regard, mutations in ADAM33 have been linked with asthma risk factors. Consequently, identifying ADAM33 pathogenic nonsynonymous single-nucleotide polymorphisms (nsSNPs) can be very importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…In recent years, whole-genome screening studies have found that ADAM33 is a key asthma susceptibility gene [4]. The detection of human biopsy specimens by Ito et al [5] showed that the expression of ADAM33 mRNA and protein in the airway smooth muscle of asthmatic patients was signi cantly higher than that of normal individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, whole-genome screening studies have found that ADAM33 is a key asthma susceptibility gene [4]. The detection of human biopsy specimens by Ito et al [5] showed that the expression of ADAM33 mRNA and protein in the airway smooth muscle of asthmatic patients was signi cantly higher than that of normal individuals.…”
Section: Introductionmentioning
confidence: 99%